Organophosphorus flame retardants in surface and effluent water samples from the Vaal River catchment, South Africa: levels and risk to aquatic life - Chokwe, TB; Mporetji, SM (Water SA, 2019)
The occurrence and risk assessment of seven organophosphorus flame retardants (OPFRs) in surface water samples within the Vaal River catchment in South Africa were investigated. Wastewater treatment works effluents as the potential sources of OPFRs in surface water were also analysed. In surface water, tris-(chloro-propyl)-phosphate (TCPP) – the total of the three TCPP isomers studied, and tris-(2, 3 dibromo-propyl)-phosphate (TDBPP) were the most abundant OPFRs, with mean concentrations of 276 ng/L and 227 ng/L; respectively. In effluent water samples, the most abundant OPFR was TCPP with a mean concentration of 700 ng/L. A high detection frequency (> 80%) was observed for six of the seven OPFRs with tris-(1, 3- dichloro-propyl)-phosphate (TDCPP) detection frequency being the lowest at 17%. Assessment of risk to aquatic organisms using risk quotients based on measured environmental concentrations (MEC) and predicted no-effect concentrations (PNEC) ranged from no significant risk (for algae, daphnia and fish) to low potential for adverse effects (for algae and fish).